2013
DOI: 10.14219/jada.archive.2013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Electronic dental record use and clinical information management patterns among practitioner-investigators in The Dental Practice-Based Research Network

Abstract: Objectives Determine the: (1) extent of computer use for managing clinical information among practitioner-investigators in The Dental Practice-Based Research Network (DPBRN); (2) type of patient information kept electronically; and (3) willingness to reuse electronic dental record (EDR) data for research. Methods Web-based survey of 991 U.S. and Scandinavian practitioner-investigators. Results 729 (74%) practitioner-investigators responded. Seventy-four percent of US solo and 78.7% of group practitioners u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
(21 reference statements)
2
30
0
1
Order By: Relevance
“…We may be able to reduce this gap as more dentists adopt EDRs, as suggested by our recent survey (13). …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We may be able to reduce this gap as more dentists adopt EDRs, as suggested by our recent survey (13). …”
Section: Discussionmentioning
confidence: 85%
“…The experience during the practice-based research network (PBRN)’s initial funding period has shown that there are more relevant research questions than can be practically addressed using the typical PBRN study approach; that some important long-term research questions do not fit very well into the timeframe of a PBRN study; and that costs and practice workflow issues limit the “throughput” of the PBRN system. Given the fact that approximately 75% of DPBRN practitioners use a computer to manage clinical information and 15% are paperless (13), secondary analysis of EDR data is increasingly compelling.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, EDRs contain most of the fields shown in the section Patient Screening and Enrollment (Schleyer et al, 2007). Our studies have shown significant growth in the amount of clinical information that dentists in the US store on computers (Schleyer et al, 2006(Schleyer et al, , 2012, making these data potentially available for research.…”
Section: Introductionmentioning
confidence: 95%
“…The overwhelming majority of dental schools in the USA have already adopted EHRs 56 In 2013, 73.8% of solo practitioners and 78.7% of dentists in group practices participating in dental practice-based research networks (DPBRNs) used computers to manage clinical information 7. Several dental EHR systems, including Dentrix, EagleSoft, and SoftDent, are used in private practice.…”
Section: Introductionmentioning
confidence: 99%